2011
DOI: 10.1038/cddis.2011.1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic function of Xbp1 as an IL-3 signaling molecule in hematopoietic cells

Abstract: Cytokine signaling is critical for proliferation, survival and differentiation of hematopoietic cell, and interleukin-3 (IL-3) is required for maintenance of many hematopoietic cell lines, such as BaF3. We have isolated apoptosis-resistant clones of BaF3 using retroviral insertional mutagenesis and the Xbp1 locus was identified as a retroviral integration site. Expression and splicing of the Xbp1 transcript was conserved in the resistant clone but was promptly disappeared on IL-3 withdrawal in parental BaF3. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 28 publications
4
45
0
12
Order By: Relevance
“…In addition, Western Blot analysis revealed that pretreatment with LY294002 abolished the IL‐17A induced up‐regulation of PI3K and AKT either total protein levels or phosphorylated protein levels respectively (* P < 0.05, ** P < 0.01) (Figure C and D). These results were similar to the results from previous studies using the same inhibitor . Taken together, the results demonstrated that the IL‐17A promoted GBM cell migration and invasion were dependent on MMP‐2/9 and Twist via activating PI3K/AKT signalling pathway.…”
Section: Resultssupporting
confidence: 90%
“…In addition, Western Blot analysis revealed that pretreatment with LY294002 abolished the IL‐17A induced up‐regulation of PI3K and AKT either total protein levels or phosphorylated protein levels respectively (* P < 0.05, ** P < 0.01) (Figure C and D). These results were similar to the results from previous studies using the same inhibitor . Taken together, the results demonstrated that the IL‐17A promoted GBM cell migration and invasion were dependent on MMP‐2/9 and Twist via activating PI3K/AKT signalling pathway.…”
Section: Resultssupporting
confidence: 90%
“…To date, it is unclear whether and how XBP1s might inhibit apoptosis. There are only two reports linking XBP1s with dedicated pro-or anti-apoptotic target genes, namely downregulation of BH3-only protein BIM (Kurata et al, 2011) or upregulation of BCL-2 (Gomez et al, 2007), respectively, and neither of these studies addressed protection from ER stress (Gomez et al, 2007;Kurata et al, 2011). In general, XBP1s-mediated protection during ER stress might rather be related to enhancement of ER folding capacity and stimulation of ERAD and/or protein secretion.…”
Section: Ire1 At the Crossroad Of Survival-death Decisionsmentioning
confidence: 99%
“…XBP1s has a diverse range of target genes which share the common aim of short term adaptation and ultimately restoration of ER function. Recent reports also suggest XBP1s signaling may be able to modulate apoptotic signaling by regulating Bcl-2 levels (Gomez et al, 2007; Kurata et al, 2011) but it remains currently unknown whether XBP1s can modulate Bcl-2 family member expression in response to ER stress. Overexpression of IRE1α in human embryonic kidney cells has been reported to induce death indicating that IRE1α could activate pro-apoptotic signaling components (Wang et al, 1998).…”
Section: Endoplasmic Reticulum Stress Apoptosis and Cell Deathmentioning
confidence: 99%